EARLY WEDDING POLEMIC AND THE IMPACT OF THE DOMESTIC VIOLENCE - Supriyanto, Edy; Eleanora, Fransiska Novita (Law and Justice, 2020)
Early marriages are increasingly prevalent and the causes are diverse, due to economic problems, promiscuity, and unpreparedness the couple take responsibility for supporting families, the impact on domestic violence, where can include due to physical violence causing injuries body, bruising or serious injury, psychic can be interpreted as cussing, glaring at causing self-esteem and mental decline, sexually interpreted to have sexual relations or rape marriage, and neglect the household and not provide for than five to ten years in a row -According and leave without breaking news. The purpose this research find the polemic of early marriage to domestic violence based on impact and consequences, the research method used is normative jurisdiction where this method refers to literature, namely by examining the literature or legislation relating to the problem under study. The results this study indicate that early marriage causes domestic violence because is triggered the impact high emotional, mental, psychological, causing violence in the domestic sphere, not only to women but also children who should receive protection and affection from parents but become victims, and Another impact is child traumatized and difficult to forget the dark events his life, because the child feels he become a victim his family.